ANALISIS KETERSEDIAAN AIR PADA DAERAH IRIGASI BLANG KARAM KECAMATAN DARUSSALAM KABUPATEN ACEH BESAR - Ichsan Syahputra; Cut Rahmawati (Jurnal Teknik Sipil Unaya, 2015)
Blang Karam Irrigation  with a total area of ± 400 Ha of rice fields have the potential to be developed which have supported such means Embung and Technical Irrigation Network. Availability of water for irrigation needs adequately met today with a reliable flow of 1.25 m3 / s and the need for retrieval of 2,312 liters / sec / ha on alternative cropping pattern with preparing land for 30 days and the need for making 0925 m3 / sec and 1,766 ltr / s / ha on alternative cropping pattern with preparing land for 45 days and the need for making 0707 m3 / sec. This suggests that the availability of water for Blang Karam irrigation area enough to meet the needs of the growing season irrigation water for 2 times a year.